Virulence Characteristic of Avian Pathogenic Escherichia coli (APEC) Isolates - Sruti Listra Adrenalin; Lynda Nugrahaning Imanjati; Ima Fauziah; Vinsa Cantya Prakasita; Sitarina Widyarini; Agnesia Endang Trihastuti Wahyuni (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
Avian pathogenic Escherichia coli (APEC) is a cause of colibacillosis in poultry, one of the respiratory disease that causes serious problems in the poultry industry. The APEC can cause high mortality and culling, decreased production, and high costs of treatment. Manifestations of colibacillosis are airsacculitis, perihepatitis, and pericarditis. The APEC serotypes that are widely identified in the field are O1K1, O2K1, and O78K80. Embryo lethality assay (ELA) is a method for determine the virulence of APEC serotypes. The aim of this study was to determine the virulence characteristic of APEC isolates. Five APEC serotypes O1K1, O2K1, O78K80, O157H7, and unknown serotype were used for ELA method by inoculated E. coli into chorioallantoic of specific pathogen free 12-days old embryos. Each group of 10 embryos, inoculated E. coli dose of 100-500 CFU/ 0,1 ml. Candling was carried out for 6 days (18-days old embryo) to determined the mortality and pathological lesions. The percentage of embryo mortality post-inoculated with APEC O1K1, O2K1, unknown serotypes were 100% (10/10), O78K80 serotype was 90% (9/10), and O157H7 serotype was 70% (70%). Lesions of all embryos were cranial and extremity hemorrhage. In this study, E. coli isolates had high virulence.